Pengaruh Keaktifan Berorganisasi Terhadap Prestasi Akademik Mahasiswa Biologi Universitas Islam Negeri Sumatera Utara - Nur Afinni, Ummi; Fadilla, Audia; Syamsia , Zia; Purnama, Fadlya (IAI Nasional Laa Roiba Bogor, 2024)
Higheri educationi isi ani importanti stagei ini ai student'si life,i wherei theyi arei expectedi toi acquirei thei necessaryi knowledgei andi skillsi toi achievei academici success.i Thei purposei ofi writingi thisi journali isi toi determinei thei effecti ofi beingi activei ini organizations,i toi findi outi thei factorsi thati influencei thei activenessi ofi organizingi Biologyi studentsi at UIN-SU and to find out that there is a relationship between organizational activity and academic achievement of Biology students at UIN-SU. This study uses a quantitative descriptive research method. The sampling technique is Random Sampling. The sample in this study were 19 Tadris Biology students at UIN-SU. Data collection techniques are through tests and non-tests. The tests are in the form of description questions to measure symbolic abilities, as well as students' understanding of